Optimization of Nasal Liposome Formulation of Venlafaxine Hydrochloride using a Box-Behnken Experimental Design - Sulekha Khute, MPharm; Rajendra K. Jangde, PhD, MPharm (Current Therapeutic Research, 2023)
ABSTRACT: Background: Intranasal administration is among the most effective alternatives to deliver drugs directly to the brain and prevent first-pass metabolism. Venlafaxine-loaded liposomes are biocompatible carriers that enhance transport qualities over the nasal mucosa. Objective: This research aimed to develop, formulate, characterize, and observe the prepared formulation. Methods: The formulation was developed using the thin-film hydration technique. The response surface plot interrelationship between three independent variables are lipid, cholesterol and polymer and four dependent variables such as particle size, percentage entrapment efficiency, and percentage drug release were ascertained using the Box-Behnken design. Results: The drug-release chitosan-coated liposomes were reported to have a particle size distribution, entanglement efficiency, and 84%, respectively, of 191 ± 34.71 nm, 94 ± 2.71% and 94 ± 2.71%. According to in vitro investigations, liposomes as a delivery system for the nasal route provided a more sustained drug release than the oral dosing form. Conclusions: The intranasal administration of venlafaxine liposomal vesicles effectively enhanced the absolute bioavailability, retention time, and brain delivery of venlafaxine.